Respon fisiologis dan hematologis Kambing peranakan Etawah terhadap cekaman panas - Enos The; M. Jen Wajo; M. A. Muin (Cassowary, 2018)
PE goat is a small ruminant crossed between Etawah goat and bean goat, which introduced in Manokwari since 2007. Livestock can well produce depend on environment comfortable temperature in the area of tropical temperature on the day is radiated in high sun light. If the goat is expose to the blazing sun, it supposed experiencing heat stress and caused to the physiological and haematological condition. The aim of this study is to know the physiological and haematological response of PE goat to heat stress. This design of research used is Split Plot (RPT). 8 goats will be a sample which devide in two groups, of unexposed groups and Groups exposed to sunlight. Each group consists of young males, young female, adult male, adult female. The variables observed included physiological aspects (heart rate, rectal temperature, respiratory rate) and haematological aspects (hemoglobin level, hematocrit value, erythrocyte count, leukocyte count). The results showed that interaction between goats and heat stress status did not influence physiological aspect variable (heart rate, rectal temperature, respiratory rate), but very significant effect on some hematological aspect variable such as hemoglobin and erythrocytes. The status of livestock has a very significant effect on some physiological aspect variable such as rectal temperature, respiratory rate) and hematological aspect variable ie hemoglobin, hematocrit and erythrocytesTreatment of heat stress has a very significant effect on the physiological aspects of variables such as heart rate, rectal temperature and respiration whereas on hematologic aspect variable have significant effect on hemoglobin level, very significant effect on hematocrit value and erythrocyte level.